The muscular organization of the stomach of Capybaira (Hydrochoerus hydrochaeris): an architectural view - Moraes, PTD; de Souza, W. M.; Neto, PBD; Barretto, CSD; Ribeiro, AACM (Urban & Fischer Verlag, 2005)
Twenty-two stomachs from adult capybaras were used in this study, and an acid digestion mesoscopic technique was pursued using different concentrations of nitric acid to observe the muscular organization of the stomach. The capybara's stomach possessed a muscular coat composed of four layers or strata: external longitudinal, external oblique, circular and internal oblique. Also, the cardiac and pyloric sphincter muscles were comprised of three or two different layers, respectively. Furthermore, the internal oblique fibres were observed extending from the cardiac portion of the stomach to the smaller curvature, where they participated in the formation of the Ansa cardiaca together with the external. longitudinal fibres. This muscular architectural arrangement was compared to that in small rodents (rat, hamster, guinea pig), as well as in rabbits and pigs. In conclusion, the stomach of the capybara has a very particular, complex and defined muscular organization that differs from that in other rodents, or domestic animals, in particular, pigs. (c) 2005 Elsevier GmbH. All rights reserved.
Keywords: rodents; stomach; Capybaras; gastric musculature